2022
DOI: 10.1111/jse.12897
|View full text |Cite
|
Sign up to set email alerts
|

Current and historical factors drive variation of reproductive traits in unisexual mosses in Europe: A case study

Abstract: Unisexual bryophytes provide excellent models to study the mechanisms that regulate the frequency of sexual versus asexual reproduction in plants, and their ecological and evolutionary implications. Here, we determined sex expression, phenotypic sex ratio, and individual shoot traits in 242 populations of the cosmopolitan moss Pseudoscleropodium purum spanning its whole distributional range. We tested whether niche differentiation, sex-specific differences in shoot size, and biogeographical history explained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…This suggests that fertilization is, to some degree, mate limited in both species and limited by male mates in D. turgescens . Mate-limited reproduction has previously been suggested based on negative correlations between strong female sex ratio bias and low sporophyte frequency (but see Boquete et al , 2023 ) and confirmed experimentally in two mosses ( Bisang et al , 2004 ).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This suggests that fertilization is, to some degree, mate limited in both species and limited by male mates in D. turgescens . Mate-limited reproduction has previously been suggested based on negative correlations between strong female sex ratio bias and low sporophyte frequency (but see Boquete et al , 2023 ) and confirmed experimentally in two mosses ( Bisang et al , 2004 ).…”
Section: Discussionmentioning
confidence: 65%
“… Chopra and Bathla, 1983 ; Rydgren and Økland, 2002 ), and geographical variation in sex phenotypes and sex expression have been demonstrated repeatedly in different plant groups ( Benassi et al , 2011 ; Yakimowski and Barrett, 2014 ; Blackstock, 2015 ; Pereira et al , 2016 ). Sex expression rates differed between different microenvironments in the desert moss Syntrichia caninervis ( Baughman et al , 2017 ; Ekwealor et al , 2022 ) and varied across Europe along macroscale environmental gradients in the perennial pleurocarpous moss Pseudoscleropodium purum ( Boquete et al , 2023 ). However, little is known about environmental effects on genotypic sexes in bryophytes (Bisang et al , 2015 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations